The evolving strategies for the management of patients with metastatic gastric cancer: A narrative review and expert opinion - Cascinu, Stefano; Di Bartolomeo, Maria; Lonardi, Sara; Beretta, Giordano; Fornaro, Lorenzo; De Vita, Ferdinando (Frontiers in Medicine, 2022)
Gastric cancer (GC) is recognized as one of the most common deadly malignancies worldwide and about 40%-50% of patients present at diagnosis with an unresectable disease due to a locally advanced or already metastatic condition. Recently, therapeutic options for management of metastatic GC (mGC) have been approved allowing a potential improvement of patient cancer treatment response and also an establishment of a continuum of care for this aggressive disease. This report is the result of a literature review by an expert panel. The aim of this document is to provide evidence, wherever it is lacking, to provide expert opinion directed at strategic management of mGC, and in particular aspect at practical management where appropriate guidelines are not available. Treatment landscape with new therapeutic strategies for third line and beyond, role of imaging, prognostic factors, symptoms and markers as well as the importance of multidisciplinary approach particularly the nutritional aspects are discussed.